Late presentation of RPE65 retinopathy in three siblings - Magliyah, Moustafa (Doc Ophthalmol, 2020)
PURPOSE: Gene therapy for RPE65 retinopathy has been recently approved. The purpose of this study was to assess retinal structure and function in 3 siblings presenting with late-stage RPE65 retinopathy and to assess the unmet need for such therapy in Saudi Arabia. METHODS: Search of the retinal dystrophy registry at King Khaled Eye Specialist Hospital and clinical examination including multimodal retinal imaging, full-field electroretinography (ERG), dark adapted full-field stimulus sensitivity thresholds, and molecular genetic testing in 3 patients. RESULTS: Nine (9) patients were identified with biallelic RPE65 mutations, corresponding to a prevalence rate of 9/187 = 5% among early onset retinal dystrophies. Of these, 3 siblings (2 male and 1 female) with RPE65 retinopathy were assessed in detail, because of an unusual, late presentation. They were all over 30 years old at the time of their most recent visits and had non-recordable ERGs. The 2 male siblings presented with poor vision and paracentral loss of the inner segment ellipsoid (ISe) and focal attenuation of the outer nuclear layer (ONL) in the macula. On the other hand, the female sibling presented with 20/100 vision with preserved foveal ISe and intact ONL throughout the macula and significantly lower light sensitivity thresholds compared to her male siblings. A homozygous missense p.Arg91Trp mutation in RPE65 was identified in all. All patients were eligible for gene therapy, demonstrating a central retinal thickness of more than 100 microns on repeated examinations. CONCLUSIONS: RPE65 retinopathy seems to be relatively common on the Arabian peninsula, and in addition it may be underdiagnosed. To the best of our knowledge, this is the first detailed presentation, including multimodal retinal imaging and electrophysiological assessment, of such patients from this region. Patients with late presentation of RPE65 retinopathy may be eligible for gene therapy, in terms of remaining retinal function and structural preservation. The therapeutic window of such therapy remains to be determined. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s10633-019-09745-z) contains supplementary material, which is available to authorized users.